What kind of country we want for our children: an analysis of media coverage of the 2017 New Zealand General Election. (3rd July 2018) - Mills, Keri; Berti, Carlo; Rupar, Verica
ABSTRACT: This article is the third in a series investigating media reporting of New Zealand elections. Based on content analysis of 510 articles published in the New Zealand Herald, and thematic analysis of a subset of news stories related to young people, the study examines media coverage of the 2017 elections by looking at the topics of news stories, presence of party policies, diversity of sources and references to social groups. Comparing the 2017 results with the results of the Herald 's coverage of 2014 elections, we register a shift towards a stronger presence of policy issues, more female voices in the reports and significantly higher reference to young people. We further investigated the high number of references to young people by conducting qualitative analysis on the subset of articles mentioning young people.